Low Bone Mineral Density in Hemophiliacs - Gebetsberger, Jennifer; Schirmer, Michael; Wurzer, Walter J.; Streif, Werner (Frontiers in Medicine, 2022)
Objective: To review the current knowledge on bone health in patients with hemophilia A and the underlying pathogenetic mechanisms. Data sources: Original research articles, meta-analyses, and scientific reviews. Data synthesis: Already in childhood, patients with hemophilia A are prone to low bone mineral density, leading to osteopenia and/or osteoporosis. Initially associated with the life style of hemophilia, today we are faced with accumulating evidence that coagulation factor VIII is involved directly or indirectly in bone physiology. Conclusion: Understanding the role of factor VIII and the mechanisms of decreased bone mineral density in hemophilia A is critically important, especially as non-factor replacement therapies are available, and treatment decisions potentially impact bone health.